2007
DOI: 10.1091/mbc.e07-06-0536
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Interaction Map of the Mitotic Spindle

Abstract: The mitotic spindle consists of a complex network of proteins that segregates chromosomes in eukaryotes. To strengthen our understanding of the molecular composition, organization, and regulation of the mitotic spindle, we performed a system-wide two-hybrid screen on 94 proteins implicated in spindle function in Saccharomyces cerevisiae. We report 604 predominantly novel interactions that were detected in multiple screens, involving 303 distinct prey proteins. We uncovered a pattern of extensive interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 55 publications
14
102
0
Order By: Relevance
“…All Cnn1 mutants were expressed as fusion proteins with the Gal4 activation domain. Yeast two-hybrid was performed as previously described to analyze for the ability to grow as a consequence of HIS3 transcription using medium lacking tryptophan, leucine and histidine (SD 2TLH) in addition to 3 mM or 10 mM aminotriazole (Wong et al 2007). …”
Section: Interaction Analysismentioning
confidence: 99%
“…All Cnn1 mutants were expressed as fusion proteins with the Gal4 activation domain. Yeast two-hybrid was performed as previously described to analyze for the ability to grow as a consequence of HIS3 transcription using medium lacking tryptophan, leucine and histidine (SD 2TLH) in addition to 3 mM or 10 mM aminotriazole (Wong et al 2007). …”
Section: Interaction Analysismentioning
confidence: 99%
“…The Dam1 complex locates along microtubules, but not at kinetochores during their microtubule lattice association Tanaka et al 2007). Subsequently this complex is loaded onto kinetochores and plays an important role, perhaps in association with the Ndc80 complex, in tethering them at microtubule plus ends Shang et al 2003;Wong et al 2007) as well as in pulling them poleward as microtubules depolymerize (Fig. 1, step 2, end-on pulling; Fig.…”
Section: Interface Of Kinetochore Microtubule Interaction: the Ndc80 mentioning
confidence: 99%
“…For several years it has been known that She1 localizes to the mitotic spindle, bud neck, spindle pole bodies, and astral MTs (Wong et al 2007(Wong et al , 2009(Wong et al , 2010. Previous work described She1's role in inhibiting dynein activity until it is required for spindle positioning in anaphase ) and showed that She1 phosphorylation by Ipl1 is required to promote spindle disassembly .…”
Section: Discussionmentioning
confidence: 99%